Optimization of PV-Grid Connected System Based Hydrogen Refueling Station - Barhoumi, El Manaa; Okonkwo, Paul C.; Zghaibeh, Manaf; Belgacem, Ikram Ben; Farhani, Slah; Bacha, Faouzi (International Conference on Control, Decision and Information Technologies (Online), 2022)
The development of green hydrogen production processes is highly praised due to its advantages in environment protection and economy growth. Within this framework, this paper discusses the feasibility of hydrogen production in grid connected photovoltaic power station. The system is based on the conversion of solar energy into electrical power and hydrogen gas. The produced electrical energy is converted into hydrogen through electrolysis process. Therefore, the produced hydrogen will be used for refueling fuel cell vehicles or any other applications. The paper discusses the economic efficiency and the optimization of the PV grid connected system for the production of hydrogen. The total capacity of the grid connected PV system is 1500 kWp. The system produces 36465 kg of hydrogen per year with an average of 400 kg/day. The Levelized cost of hydrogen production is 4.2 €/kg. The estimated cost of the project depends on the cost of civil works, PV systems, electrolysers, and hydrogen tanks.